Kinetic and structural evidence for specific DMSO interference with reversible binding of uncharged bis-oximes to hAChE and their reactivation kinetics of OP-hAChE - Kolić, Dora; Gerlits, Oksana; Kucharski, Megan; Gorecki, Lukas; Joiner, Nichole; Kovalevsky, Andrey; Radić, Zoran (Chemico-biological interactions, 2025)
The structural basis of inhibitory effect of organic solvent dimethyl sulfoxide (DMSO) on human acetylcholinesterase (EC 3.1.1.7; hAChE) was inferred from the effect of DMSO on kinetics of reversible inhibition of uncharged, heterocyclic bis-oximes to hAChE, from DMSO effect on rates of reactivation of inactive organophosphate (OP)-hAChE conjugates by bis-oximes and by X-ray structures of bis-oxime and DMSO binding to hAChE. The reversible inhibition constant of DMSO for hAChE in 0.1 M phosphate buffer pH 7.4 at 22 °C, was Ki= (0.32 ± 0.04) % (or 45 ± 5 mM). The Ki of the bis-oxime LG-703 for hAChE was 3.2-fold larger in 1 % DMSO, consistent with direct competition between LG-703 and DMSO. The X-ray structure of the LG-703∗hAChE complex (PDB ID: 6U3P) shows DMSO and LG-703 bound to individual hAChE monomers, LG-703 in the chain A and DMSO in the chain B. In the co-crystallization both small molecules were present at a similar excess over their corresponding Ki values for hAChE (7.8-fold for DMSO and 6.5-fold for LG-703) and formation of two different complexes (DMSO∗hAChE and LG-703∗hAChE), in the same crystal, appears consistent with inhibition kinetics. Furthermore, rates of reactivation of paraoxon-inhibited hAChE (POX-hAChE) and of VX-hAChE by LG-703 and by a novel heterocyclic bis-oxime LG-1922 were reduced 2 - 3-fold in DMSO, consistent with observation of the active-center-bound DMSO molecules in the newly solved structure of the LG-1922∗POX-hAChE complex presented here and in our POX-hAChE structure (PDB ID: 8DT2) showing obstruction of the reactivator access to the conjugated P atom.
Keywords: oximy; VX; vazba proteinů; Antidotes; krystalografie rentgenová; dimethylsulfoxid; Crystallography, X-Ray; Protein Binding; Humans; Acetylcholinesterase; lidé; Dimethyl Sulfoxide; acetylcholinesterasa; Kinetics; Organic solvent; Acetylcholinesterase inhibition; vazebná místa; kinetika; Heterocyclic bis-oximes; Cholinesterase Inhibitors; DMSO; Binding Sites; cholinesterasové inhibitory; Paraoxon; Oximes; Acetylcholinesterase reactivation; Organophosphorus compounds